2022
DOI: 10.1038/s41398-022-01891-4
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and mitochondrial DNA copy number in bipolar disorder: identification of a subgroup of young individuals with accelerated cellular aging

Abstract: The 10–15-years decrease in life expectancy observed in individuals with bipolar disorder (BD) has been linked to the concept of accelerated cellular aging. Telomere length (TL) and mitochondrial DNA copy number (mtDNAcn) have been proposed as markers of cellular aging and comparisons between individuals with BD and healthy controls (HC) sometimes led to conflicting results. Previous studies had moderate sample sizes and studies combining these two markers into a single analysis are scarce. Using quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
2
7
2
Order By: Relevance
“…According to Köse Çinar (2017), late-stage patients have shorter TL than early-stage patients and controls (Köse Çinar 2017). Spano et al showed that the relatively short telomere length in bipolar patients might be an essential criterion to distinguish patients from healthy individuals (AUC; 0.904) (Spano et al 2022a). When we look at these studies, as in our study, telomere length was found to be short in patients with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…According to Köse Çinar (2017), late-stage patients have shorter TL than early-stage patients and controls (Köse Çinar 2017). Spano et al showed that the relatively short telomere length in bipolar patients might be an essential criterion to distinguish patients from healthy individuals (AUC; 0.904) (Spano et al 2022a). When we look at these studies, as in our study, telomere length was found to be short in patients with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study also found a difference in the correlation between GrimAge and chronological age, especially for the earliest age group between BD/non-SA and BD/SA in the replication cohort and between BD/SA and controls in the discovery cohort. This suggests that GrimAgeAccel may already be detected in young individuals with a history of SA, which coincides with previous observation of shorter telomere length and lower mitochondrial DNA copy numbers in a subgroup of young BD individuals [87].…”
Section: (Which Was Not Certified By Peer Review) Preprintsupporting
confidence: 91%
“…Multiple publications have shown increased mtDNA in maternal circulation and cord blood in pregnancies affected by PE, PE/IUGR, and IUGR [ 50 , 51 ]. Contrarily, the quality of mitochondrial quality and mtDNA copy number is significantly reduced in ageing cells [ 52 , 53 , 54 ]. This study did not provide evidence of increased mtDNA copy numbers in PE, PE associated with IUGR, and IUGR, and based on this surrogate marker of mitochondrial dysfunction, we propose that mitochondrial dysfunction is not a significant contributor to the heterogeneity evident in our study.…”
Section: Discussionmentioning
confidence: 99%